1999
DOI: 10.1074/jbc.274.40.28206
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ionization Mass Spectrometric Determination of the Molecular Mass of the ∼200-kDa Globin Dodecamer Subassemblies in Hexagonal Bilayer Hemoglobins

Abstract: The giant extracellular HBL 1 Hbs found in most terrestrial, aquatic, and marine annelids and in deep sea annelids and vestimentiferans are ϳ3.6-MDa complexes of globin subunits and nonglobin, linker chains and represent a summit of complexity for oxygen-binding heme proteins (1-4). The most extensively studied complex is the Hb from the common earthworm Lumbricus terrestris. Based on the finding of a ϳ200-kDa globin subassembly upon mild, partial dissociation of the Hb at neutral pH, a "bracelet" model of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…In general, the variation was small, the maximum decrease in mass being ϳ1.3% over the range 60 -160 V. At a given cone voltage, the observed masses of the subassembly were within experimental error of one another irrespective of the pH. Table 4 shows how the mean mass of the subassembly (n ϭ 3-5) varied with the declustering potential over the range 60 -160 V. The overall mass of the subassembly is dependent on the declustering potential, comparable to the effect observed earlier for similar subassemblies of Lumbricus and Arenicola HBL Hbs [19]. Declustering occurs when the positively charged protein ions are accelerated through a region that is intermediate in pressure between their generation at atmospheric pressure and analysis under high vacuum.…”
Section: Resultssupporting
confidence: 77%
“…In general, the variation was small, the maximum decrease in mass being ϳ1.3% over the range 60 -160 V. At a given cone voltage, the observed masses of the subassembly were within experimental error of one another irrespective of the pH. Table 4 shows how the mean mass of the subassembly (n ϭ 3-5) varied with the declustering potential over the range 60 -160 V. The overall mass of the subassembly is dependent on the declustering potential, comparable to the effect observed earlier for similar subassemblies of Lumbricus and Arenicola HBL Hbs [19]. Declustering occurs when the positively charged protein ions are accelerated through a region that is intermediate in pressure between their generation at atmospheric pressure and analysis under high vacuum.…”
Section: Resultssupporting
confidence: 77%
“…Otherwise, the masses of the tetramers would be higher than expected which is not the case. The adducts are possibly addition of water molecules, ammonium, or alkali metal ions and appear to be fairly typical of noncovalent assemblies analyzed by ESI-MS (27). Also apparent in Fig.…”
Section: Figmentioning
confidence: 89%
“…With the development of new ionization techniques such as matrix-assisted laser desorption ionization (28) and electrospray ionization (29), and the coupling of these to time-of-flight analyzers, the detectable mass range of macromolecular systems by mass spectrometry has been enhanced extensively (30,31). Moreover, the relatively gentle phase transfer from solution to the gas phase, realized especially by electrospray ionization, has allowed the intact detection by mass spectrometry of larger multiprotein assemblies (32)(33)(34)(35). Several recent examples (36 -41) have revealed that biologically relevant parameters concerning multiprotein assemblies may now be investigated by mass spectrometry, and examples include protein complex topology, protein-ligand and protein-protein binding constants, and protein complex stability.…”
mentioning
confidence: 99%